THE EFFECTS OF DIRECT AND INDIRECT WRITTEN CORRECTIVE FEEDBACK ON FRENCH WRITING SKILLS: A COMPARATIVE STUDY - Bima, Alifia Jihan Anandani; Sunendar, Dadang; Darmawangsa, Dante (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Written corrective feedback (WCF) in second-language writing studies has been conducted over the last two decades to investigate whether it has a positive or negative impact on students' writing skills. Teachers can use direct WCF or indirect WCF strategies to provide this feedback. However, conflicting views still exist on which WCF strategy is most effective in improving second language writing skills. This study aims to examine the effects of implementing direct and indirect written corrective feedback on the enhancement of French writing skills. The research employed a quantitative approach utilizing a static-group pre-test and post-test design. The participants in this study consisted of fifty-six students enrolled in the French Language Education Study Program at a public university in Bandung, Indonesia. They were divided into two experimental groups, referred to as the direct and indirect written corrective feedback groups. They were assessed through a writing test for French narrative texts. The collected data were analyzed using SPSS, employing normality and homogeneity tests, as well as the N-Gain test and Mann-Whitney U test which aimed to determine the average differences and their significance. The findings indicated that the direct written corrective feedback group exhibited a significantly greater improvement (N-Gain score: 0.3229) compared to the indirect written corrective feedback group (N-Gain score: 0.1174). Nonetheless, the statistical analysis utilizing the Mann-Whitney U test found no significant difference in the N-Gain scores between the two WCF classes (p0.05). The results of this research are expected to contribute to second language writing studies and provide insights for teachers in teaching writing in French as a foreign language.